2016
DOI: 10.1007/s11904-016-0312-1
|View full text |Cite
|
Sign up to set email alerts
|

PrEP as Peri-conception HIV Prevention for Women and Men

Abstract: Daily oral tenofovir (TDF)-based pre-exposure prophylaxis (PrEP) is an effective HIV prevention strategy and recommended for men and women with substantial risk of HIV acquisition. The peri-conception period, the stage prior to pregnancy when condom use is necessarily reduced, has elevated HIV risk that can be mitigated by PrEP use. Data from a randomized trial suggest that peri-conception PrEP use by HIV-seronegative women does not increase the risk of pregnancy loss, birth defects or congenital anomalies, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 69 publications
0
45
0
Order By: Relevance
“…In PrEP as a bridge to ART strategy, PrEP is ofered to HIV-uninfected person as a 'bridge' to ART in the discordant partnership-that is, until ART initiation by the HIVinfected partner and for the irst 6 months after ART is started or viral suppression. This strategy demonstrated nearly elimination of HIV transmission within serodiscordant couples in Uganda and Kenya [29].…”
Section: Discussionmentioning
confidence: 99%
“…In PrEP as a bridge to ART strategy, PrEP is ofered to HIV-uninfected person as a 'bridge' to ART in the discordant partnership-that is, until ART initiation by the HIVinfected partner and for the irst 6 months after ART is started or viral suppression. This strategy demonstrated nearly elimination of HIV transmission within serodiscordant couples in Uganda and Kenya [29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with the increasing popularity of integrase strand inhibitors (INSTIs) and recent FDA approval of tenofovir alafenamide (TAF), which is expected to have fewer side effects than TDF, the landscape of ART in pregnancy is likely to change again. Finally, there will be growing antiretroviral exposure among HIV-uninfected women with the use of pre-exposure prophylaxis (PrEP) [50]. …”
Section: In-utero Antiretroviral Therapy Exposurementioning
confidence: 99%
“…However, PrEP trials excluded pregnant women from enrolment, and those who fell pregnant during these studies were discontinued from PrEP [11, 14]. A recent systematic review demonstrated that PrEP was not associated with increased pregnancy-related adverse events, and no studies have found adverse effects among infants exposed to tenofovir disoproxil fumarate (TDF) as part of treatment for HIV-infected women during pregnancy [15, 1921] or breastfeeding [16, 22, 23]. In addition, our studies in South Africa demonstrated that the use of tenofovir during pregnancy was not associated with adverse events among infants [20, 21].…”
Section: Introductionmentioning
confidence: 99%